Three-dimensional evaluation of conventional anterior open bite treatment with bonded spurs associated with build-ups versus conventional bonded spurs: a randomized clinical trial with 24-month follow-up - Jorge, Demi Lisbôa Dahás (2021)
Objective: To compare the dentoalveolar effects of early treatment of anterior open bite with bonded spurs associated with build-ups versus conventional bonded spurs by three-dimensional superimposition of digital models after 24 months. Material and Methods: Fifty patients between 7 and 11 years of age with anterior open bite were prospectively and randomly assigned to one of two study groups. The experimental group (G1) consisted of 25 patients treated with bonded spurs associated with buildups. The control group (G2) consisted of 25 patients treated with conventional bonded spurs. Digital dental models, acquired from intraoral scanning of the dental arches, were captured at baseline (T1) and after 24 months of treatment (T2). Superimposition of the T1 and T2 digital models was performed in the 3D SlicerCMF program, based on landmarks and regions of interest. Three-dimensional linear distances and the amount of directional changes in each plane of the 3D space (x, y, and z axes: laterallateral or transverse, anteroposterior or sagittal and superior-inferior or vertical, respectively) were measured. When normality was verified, intergroup comparisons were performed with t tests (P<0.05). Results: G1 included 22 patients and the G2 comprised 24 patients. After 24 months of treatment patients showed improvements in the overbite and there was no statistically significant intergroup difference in maxillary central and lateral incisors and molar changes. Conclusions: Both protocols showed similar 3D changes in maxillary incisors and molars after 24 months of treatment. Superimposition of digital dental models showed similar extrusion, medial and forward displacement of the maxillary incisors and similar extrusion, buccal and forward displacement of the maxillary molars for both groups, after 24 months of treatment. A treatment period of 24 months of AOB provides greater efficiency than a 12-month period.